2011
DOI: 10.1007/s00787-010-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention for at risk children: 3-year follow-up

Abstract: International audienceChildhood behavioral and emotional symptoms are linked with distress and dysfunction that may persist into adulthood. Effective and practical early prevention could make a significant contribution to the well-being of individuals and the functioning of communities. School-based targeted interventions are relatively easy and inexpensive to deliver and have been shown to reduce symptoms in the short term. The current study evaluates the 2- and 3-year outcome of targeted school-based drama g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…All qualitative studies used a single-group design, and the number of participants ranged from three to 40 ( M = 17, SD = 20.07). Two studies followed up the participants: a study about drama therapy and children at risk followed participants for 3 years after the posttest (McArdle et al, 2011), and a case study about a young girl with selective mutism performed a 1-year follow-up (Oon, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All qualitative studies used a single-group design, and the number of participants ranged from three to 40 ( M = 17, SD = 20.07). Two studies followed up the participants: a study about drama therapy and children at risk followed participants for 3 years after the posttest (McArdle et al, 2011), and a case study about a young girl with selective mutism performed a 1-year follow-up (Oon, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…(midrange) risk of bias in all domains (McArdle et al, 2011); the study that examined the effectiveness of drama therapy in improving speech and academic performance presented a mix of unclear and low risk of bias in the different domains (Rajabi et al, 2013); the study that examined the effectiveness of drama therapy for people with dementia presented high risk of bias in most of the domains (Mechaeil, Graybow, & Cobham, 2010); and the study that used drama therapy in preparation for a medical procedure presented a mixture of high, unclear, and low risk of bias across domains (Ilievová et al, 2015). None of the four studies was identified as having a low risk of bias across all six domains.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Such evaluations have been carried out elsewhere and across a range of settings. These include studies of school‐based peer support programmes (Cowie et al , 2002), interventions to reduce childhood behavioural and emotional symptoms (McArdle et al , 2011) and the treatment of young abusers (Masson et al , 2013). This work is the exception though.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that drama therapy is a valuable intervention expanding the possibilities of working with young offenders (Hanna & Hunt, 1999). Drama group therapy intervention's effectiveness was evaluated through the randomized controlled trial among students at risk for emotional and behavioural problems (McArdle, et al, 2011); and among students with high aggressive behaviour (Karataş & Gökçakan, 2009a;2009b) showing reduction of behavioural symptoms and total aggression respectively.…”
Section: Problem Statementmentioning
confidence: 99%